2016
DOI: 10.1080/10245332.2016.1219497
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the pathophysiology of primary immune thrombocytopenia

Abstract: A better understanding of the immunomodulatory effects of each ITP therapy is needed to best manage the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 97 publications
0
57
1
3
Order By: Relevance
“…[13] The serum levels of TGFβ level was significantly decreased in Li W et al However, after the treatment by immunosuppressive therapy, TGFβ was down-regulated[14] which is not consistent with our results.…”
Section: Discussion:-contrasting
confidence: 53%
“…[13] The serum levels of TGFβ level was significantly decreased in Li W et al However, after the treatment by immunosuppressive therapy, TGFβ was down-regulated[14] which is not consistent with our results.…”
Section: Discussion:-contrasting
confidence: 53%
“…Therefore, PAF and cytokines potentiate each other's effects in vivo to modulate the immune response [39]. The strong associations were found between PAF and IL-6, between PAF and IL-10, between PAF and CRP, revealing the PAF, interacting with IL-6 and IL-10, are jointly responsible for thrombocytopenia [25].…”
Section: Discussionmentioning
confidence: 98%
“…Abbreviations: AUC, areas under curve. [22][23][24][25][26][27][28][29][30] cells [50,51], they may closely related to the platelet destruction. Therefore, we used the levels of cytokines as a stratification variable for EFS, the results showed that cytokine play a significant role in EFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rituximab exerts its therapeutic effect in ITP mainly through depletion of pre-plasma B cells, thus decreasing autoantibody production [32]. In addition, rituximab could correct the number and dysfunction of the T-cell compartment in ITP patients [33][34][35]. The reason why ITP patients with ANAs could achieve a higher overall response rate remains unknown.…”
Section: Discussionmentioning
confidence: 99%